Increasing The Ability To Recognize Number Symbols Through The Activities Of Playing Snakes And Stairs For Children Of Group A In Tk Aisyiyah Busthanul Athfal 6 Candi: Peningkatan Kemampuan Mengenal Lambang Bilangan Melalui Kegiatan Bermain Ular Tangga Pada Anak Kelompok A Di Tk Aisyiyah Busthanul Athfal 6 Candi - Retno Nur Hardani; Luluk Iffatur Rocmah (Academia Open, 2021)
This research is motivated by the lack of ability of group A children in Kindergarten Aisyiyah Busthanul Athfal 6 Candi in recognizing the symbol of numbers. Based on a preliminary study in Kindergarten Aisyiyah Busthanul Athfal 6 Temple found that 70.59% of 17 Kindergarten A children were still wrong in recognizing good symbols when asked to say by sorting number cards, dancing lines according to the number of drawings, counting many marbles and pasting numbers right. These problems are caused by the introduction of non-matching number symbols, and non-concrete learning media (using worksheets). The solution provided is the introduction of the number symbol by playing snakes and ladders with steps to recognize the symbol number. This research is a classroom action research (CAR) that uses Kemmis and Mc. Taggart. The subject of the action was the children of group A "Kindergarten Aisyiyah Busthanul Athfal 6 Candi, totaling 17 children, each with 13 boys and 4 girls. In this study using three stages, namely pre cycle, cycle I, and cycle II. The results of this study that have been carried out to improve the ability to recognize child group A symbols in Aisyiyah Busthanul Athfal 6 Kindergarten Temple show that the ability to recognize child number symbols from pre-cycle, cycle I, and cycle II has increased. In the pre-cycle completeness the overall value of group A was 29.41%, the first cycle completeness the overall value of group A was 52.94%, and in the second cycle the completeness value of group A was 82.35%. This proves that there is an increase in the ability to recognize child number symbols after a study using a snake ladder game in learning material.